Translating Radio Telephony Communication (RTF) for Indonesian Speaker: A Case Study of Pilot-ATC Communication in Indonesian Airspace - Darmawan Jaladri Saputra; Dimas Adika (Universitas Sebelas Maret, 2024)
This research study focuses on the translation of Radio Telephony Communication (RTF) for Indonesian speakers, specifically examining pilot-air traffic controller (ATC) communication in the airspace of Indonesia. The objective is to explore the key phrases utilized in RTF and their accurate translation to facilitate comprehension by Indonesian pilots and ATCs. Through a meticulous case study conducted in Indonesian aviation settings, the challenges encountered in translating these phrases within the RTF context are identified and addressed. The findings reveal the complexities of translating complex sentence structures and technical vocabulary, which often require a combination of literal translation, adaptation, and paraphrasing strategies. The study highlights the importance of understanding the cultural and linguistic nuances of both English and Indonesian languages, as well as the specific context of pilot-ATC communication. By employing appropriate translation strategies, such as adapting certain technical terms to align with Indonesian language conventions while ensuring accuracy and clarity, the translation process can effectively enhance communication effectiveness and safety in pilot-ATC interactions. The results of this study provide valuable insights and recommendations for professionals involved in the translation of RTF in Indonesia, ultimately contributing to the improvement of aviation communication practices.